PERLINDUNGAN HUKUM TERADAP PASIEN YANG MEMPEROLEH PELAYANAN KESEHATAN BERBASIS ONLINE - Asad Awaluddin, Muhammad; Warka, Made; Budiarsih, Budiarsih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
One part of telemedicine is the existence of a website-based health clinic service then written online clinic, in this online clinic patients can consult with doctors through the internet about the disease problems suffered by patients and even doctors can diagnose the patient's condition without doing anamesis and examination directly physical, but also can buy drugs directly from the online clinic with the advice of doctors who diagnose the patient concerned and the delivery of the drug was carried out by express delivery services. So it is interesting to study how the responsibility of doctors who have provided health services online if the patient receives a loss. The type of research I use is normative juridical, i.e. legal research conducted by examining library materials or secondary data. Normative legal research is carried out on laws and regulations relating to legal protection of patients who obtain online-based health services. This research is a kind of analytical descriptive research, which describes the applicable laws and regulations or positive law related to legal theory and practice of implementing positive law in society.